Instantaneous and Noninstantaneous Impulsive Integrodifferential Equations in Banach Spaces - Saïd Abbas; Mouffak Benchohra; Gaston M. N'Guérékata (Abstract and Applied Analysis)
This paper deals with some existence of mild solutions for two classes of impulsive integrodifferential equations in Banach spaces. Our results are based on the fixed point theory and the concept of measure of noncompactness with the help of the resolvent operator. Two illustrative examples are given in the last section.